High-capacity carbon-coated coal-based hard carbon material, preparation method thereof, negative pole piece and sodium ion battery

High-capacity carbon-coated coal-based hard carbon materials are prepared through acid-base purification and high-temperature cross-linking reaction, which solves the problems of increased capacity and reduced cost of hard carbon negative electrode materials, and realizes negative electrode materials with high capacity and excellent electrochemical performance in sodium ion batteries .

CN119306205APending Publication Date: 2025-01-14ZHENGZHOU BAK ELECTRONICS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411419178.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The capacity of hard carbon negative electrode materials is difficult to increase and the cost is high, which limits its application in sodium ion batteries.

Method used

The preparation method of high-capacity carbon coated coal-based hard carbon material is adopted. The coal powder after acid-base purification and drying is reacted with sodium gluconate under heating conditions to form a highly uniform closed-pore hard carbon material, which improves its electrochemical performance. .

Benefits of technology

The reversible specific capacity and first effect of hard carbon materials have been significantly improved, and the charging specific capacity of the first round reaches 301.5mAh g-1, showing excellent electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306205A_ABST
    Figure CN119306205A_ABST
Patent Text Reader

Abstract

The invention relates to a high-capacity carbon-coated coal-based hard carbon material and a preparation method thereof, a negative pole piece and a sodium ion battery. The preparation method of the high-capacity carbon-coated coal-based hard carbon material comprises the following steps: grinding a coal-based material to obtain coal powder, carrying out acid-base purification and drying treatment on the coal powder to obtain impurity-removed coal powder, adding the impurity-removed coal powder and sodium gluconate into a solvent, reacting under a heating condition to obtain a suspension, and drying the suspension to obtain the high-capacity carbon-coated coal-based hard carbon material. And drying and carbonizing the turbid liquid to obtain the product. Sodium gluconate is uniformly dispersed on the surface of coal powder through a liquid phase, then hydroxyl on sodium gluconate and carboxyl of coal are subjected to a cross-linking reaction in the carbonization process to generate an ester group, and the existence of the ester group in the carbonization process increases inner holes of the hard carbon material and reduces the specific surface area of the hard carbon material; further, the reversible specific capacity and the first efficiency of the coal-based hard carbon negative electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a high-capacity carbon-coated coal-based hard carbon material, a preparation method thereof, a negative electrode plate and a sodium ion battery. Background Art

[0002] Sodium-ion batteries are mainly composed of positive electrode materials, positive current collectors, negative electrode materials, negative current collectors, separators and electrolytes. Among them, negative electrode materials, as an important component of sodium-ion batteries, play a decisive role in the energy density, cycle performance and safety performance of batteries. At present, the more mature negative electrode materials are mainly hard carbon, soft carbon, graphite, etc. Among them, hard carbon is expected to be mass-produced due to its low cost, rich precursor sources and high safety. For the preparation of hard carbon negative electrodes, the selection of precursors is crucial, so coal with high carbon yield and low cost is regarded as a hard carbon precursor with high economic value. However, the capacity of hard carbon is difficult to improve. If coal-based hard carbon is to be further developed into a commercially available negative electrode material, its cost must be further reduced and its electrochemical performance must be improved. Summary of the invention

[0003] The first object of the present invention is to provide a high-capacity carbon-coated coal-based hard carbon material to solve the technical problem that the capacity of hard carbon is difficult to improve.

[0004] The second object of the present invention is to provide a method for preparing a high-capacity carbon-coated coal-based hard carbon material.

[0005] The third object of the present invention is to provide a negative electrode plate.

[0006] A fourth object of the present invention is to provide a sodium ion battery.

[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is:

[0008] A method for preparing a high-capacity carbon-coated coal-based hard carbon material comprises the following steps: grinding the coal-based material to obtain coal powder, subjecting the coal powder to acid-base purification and drying treatment to obtain impurity-removed coal powder, adding the impurity-removed coal powder and sodium gluconate to a solvent and reacting them under heating conditions to obtain a suspension, and drying and carbonizing the suspension to obtain the obtained product.

[0009] Furthermore, the mass ratio of the coal powder after impurities removal to the sodium gluconate is 1:0.8 to 1:1; the solvent is water, and 30 to 60 mL of the solvent is added for every gram of the coal powder after impurities removal.

[0010] Furthermore, the reaction temperature of the impurity-removed coal powder and the sodium gluconate is 50-150° C., and the reaction time is 1-4 hours.

[0011] Furthermore, the carbonization is carried out under an inert gas, and the steps of the carbonization are: keeping warm at 200-350° C. for 1-4 hours, and then carbonizing at 1200-1500° C. for 1-3 hours.

[0012] Furthermore, the inert gas is argon.

[0013] Furthermore, the step of acid-base purification and drying is: washing the coal powder with an acid solution and then washing it with water until it is neutral, washing it with an alkali solution and then washing it with water until it is neutral, and then drying it.

[0014] Furthermore, the coal-based material is bituminous coal; the coal-based material is ball-milled to obtain coal powder, and the coal powder is sieved through a 100-400 mesh sieve, dried, and then subjected to acid-base purification and drying treatment.

[0015] A high-capacity carbon-coated coal-based hard carbon material is prepared by using the above-mentioned method for preparing the high-capacity carbon-coated coal-based hard carbon material.

[0016] A negative electrode plate comprises the above-mentioned high-capacity carbon-coated coal-based hard carbon material.

[0017] A sodium ion battery comprises the above-mentioned negative electrode plate.

[0018] Beneficial effects of the present invention:

[0019] The present invention evenly disperses sodium gluconate on the surface of coal powder through the liquid phase, and then during the carbonization process, the hydroxyl groups on the sodium gluconate react with the carboxyl groups of the coal to produce ester groups. During the carbonization process, the presence of the ester groups increases the inner pores of the hard carbon material and reduces the specific surface area of ​​the hard carbon material, thereby improving the reversible specific capacity and the first effect of the coal-based hard carbon negative electrode material.

[0020] The present invention obtains a highly uniform closed-pore hard carbon negative electrode material through liquid phase mixing and high-temperature cross-linking reaction. The hard carbon negative electrode material has a high initial efficiency and specific capacity. The negative electrode sheet using the high-capacity carbon-coated coal-based hard carbon material of the present invention exhibits excellent electrochemical performance, increasing the reversible capacity to 301.5 mAh g -1 .

[0021] The negative electrode sheet prepared by the high-capacity carbon-coated coal-based hard carbon material of the present invention is a sodium ion battery assembled with 1M NaPF6 (sodium hexafluorophosphate) EC / DEC (ethylene carbonate / diethyl carbonate) as the electrolyte. -1 At a current density of 1.5 mAh g, the first cycle charge capacity reaches 301.5 mAh g -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 XRD diagrams of high-capacity carbon-coated coal-based hard carbon materials in Example 1 and Comparative Example 9;

[0023] Figure 2 The voltage capacity curve diagram of the high capacity carbon-coated coal-based hard carbon material in Example 1 and Comparative Example 9;

[0024] Figure 3 This is a SEM image of the high-capacity carbon-coated coal-based hard carbon material in Example 1;

[0025] Figure 4 This is a SEM image of the high-capacity carbon-coated coal-based hard carbon material in Comparative Example 9;

[0026] Figure 5 The voltage capacity curve of the high capacity carbon-coated coal-based hard carbon material of Comparative Examples 1-4;

[0027] Figure 6 The voltage capacity curve diagram of the high capacity carbon-coated coal-based hard carbon material of Comparative Examples 5-8;

[0028] Figure 7 These are the nitrogen adsorption isotherms of the high-capacity carbon-coated coal-based hard carbon materials of Example 1 and Comparative Example 9. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with the embodiments of the present invention and the accompanying drawings.

[0030] Example 1 and Comparative Examples 1-9 all use copper foil as a hard carbon current collector, and the electrolyte, diaphragm and hard carbon current collector are assembled into button-type sodium ion batteries in a glove box with argon and water content below 0.01 ppm. The diaphragm is glass fiber, and the electrolyte is 1MNaPF6 EC / DEC (vol%: 1:1).

[0031] Example 1

[0032] The method for preparing the high-capacity carbon-coated coal-based hard carbon material of Example 1 comprises the following steps:

[0033] S1: Grind the bituminous coal in a ball mill for 10 h to obtain coal powder, 10 g of the coal powder was passed through a 200 mesh sieve, and then placed in a vacuum drying oven at 120 °C for 12 h;

[0034] S2: Add the dried coal powder into a flask containing 200 mL of 5M hydrochloric acid solution, place the flask in an oil bath, set the temperature to 80°C and use mechanical stirring. A condenser tube needs to be installed on the flask to remove inorganic impurities. After reacting for 12 hours, filter and wash with deionized water until neutral to obtain solid particles;

[0035] S3: Add the solid particles into a beaker containing 200 mL of 5M NaOH solution, place the beaker in an oil bath and heat to 80°C, seal the beaker with plastic wrap, stir the mixture under magnetic stirring for 12 hours, filter and wash with deionized water until neutral, and dry under vacuum at 120°C to obtain the impurity-free coal powder;

[0036] S4: Add 5 g of the impurity-removed coal powder and 5 g of sodium gluconate into a beaker containing 200 mL of deionized water, react in an oil bath at 100°C for 2 h to obtain a suspension, dry the suspension for 12 h, and then vacuum dry it for 12 h to obtain a sample powder;

[0037] S5: The sample powder in S4 is pressed into a sheet-like sample by a die press at 20 MPa;

[0038] S6: The sample in S5 is placed in a tubular furnace under an argon atmosphere for carbonization. The carbonization conditions are: keeping the temperature at 350°C for 1 hour, then raising the temperature to 1300°C and carbonizing for 2 hours.

[0039] Example 2

[0040] The method for preparing the high-capacity carbon-coated coal-based hard carbon material of Example 2 comprises the following steps:

[0041] S1: Grind the bituminous coal in a ball mill for 10 h to obtain coal powder, 10 g of the coal powder was passed through a 100-mesh sieve, and then placed in a vacuum drying oven at 120°C for 12 h;

[0042] S2: Add the dried coal powder into a flask containing 200 mL of 5M hydrochloric acid solution, place the flask in an oil bath, set the temperature to 80°C and use mechanical stirring. A condenser tube needs to be installed on the flask to remove inorganic impurities. After reacting for 12 hours, filter and wash with deionized water until neutral to obtain solid particles;

[0043] S3: Add the solid particles into a beaker containing 200 mL of 5M NaOH solution, place the beaker in an oil bath and heat to 80°C, seal the beaker with plastic wrap, stir the mixture under magnetic stirring for 12 hours, filter and wash with deionized water until neutral, and dry under vacuum at 120°C to obtain the impurity-free coal powder;

[0044] S4: 5 g of the impurity-removed coal powder and 4 g of sodium gluconate were added to a beaker containing 200 mL of deionized water, and reacted in an oil bath at 150° C. for 4 h to obtain a suspension, which was then dried for 12 h and then vacuum dried for 12 h to obtain a sample powder;

[0045] S5: The sample powder in S4 is pressed into a sheet-like sample by a die press at 20 MPa;

[0046] S6: The sample in S5 is placed in a tubular furnace under an argon atmosphere for carbonization. The carbonization conditions are: keeping the temperature at 200°C for 1 hour, then raising the temperature to 1500°C and carbonizing for 1 hour.

[0047] Example 3

[0048] The method for preparing the high-capacity carbon-coated coal-based hard carbon material of Example 2 comprises the following steps:

[0049] S1: Grind the bituminous coal in a ball mill for 10 h to obtain coal powder, 10 g of the coal powder was passed through a 400-mesh sieve, and then placed in a vacuum drying oven at 120°C for 12 h;

[0050] S2: Add the dried coal powder into a flask containing 200 mL of 5M hydrochloric acid solution, place the flask in an oil bath, set the temperature to 80°C and use mechanical stirring. A condenser tube needs to be installed on the flask to remove inorganic impurities. After reacting for 12 hours, filter and wash with deionized water until neutral to obtain solid particles;

[0051] S3: Add the solid particles into a beaker containing 200 mL of 5M NaOH solution, place the beaker in an oil bath and heat to 80°C, seal the beaker with plastic wrap, stir the mixture under magnetic stirring for 12 hours, filter and wash with deionized water until neutral, and dry under vacuum at 120°C to obtain the impurity-free coal powder;

[0052] S4: Add 5 g of the impurity-removed coal powder and 6 g of sodium gluconate into a beaker containing 200 mL of deionized water, react in an oil bath at 150° C. for 1 h to obtain a suspension, dry the suspension for 12 h, and then vacuum dry it for 12 h to obtain a sample powder;

[0053] S5: The sample powder in S4 is pressed into a sheet-like sample by a die press at 20 MPa;

[0054] S6: The sample in S5 is placed in a tubular furnace under an argon atmosphere for carbonization. The carbonization conditions are: keeping the temperature at 300°C for 1 hour, then raising the temperature to 1200°C and carbonizing for 3 hours.

[0055] Comparative Example 1

[0056] The preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 1 comprises the following steps:

[0057] S1: Grind the bituminous coal in a ball mill for 10 h to obtain coal powder, 10 g of the coal powder was passed through a 200-mesh sieve, and then placed in a vacuum drying oven at 120°C for 12 h;

[0058] S2: Add the dried coal powder into a flask containing 200 mL of 5M hydrochloric acid solution, place the flask in an oil bath, set the temperature to 80°C and use mechanical stirring. A condenser tube needs to be installed on the flask to remove inorganic impurities. After reacting for 12 hours, filter and wash with deionized water until neutral to obtain solid particles;

[0059] S3: Add the solid particles into a beaker containing 200 mL of 5M NaOH solution, place the beaker in an oil bath and heat to 80°C, seal the beaker with plastic wrap, stir the mixture under magnetic stirring for 12 hours, filter and wash with deionized water until neutral, and dry under vacuum at 120°C to obtain the impurity-free coal powder;

[0060] S4: Add 5 g of coal powder and 5 g of sodium gluconate into a beaker containing 200 mL of deionized water, react in an oil bath at 100 °C for 2 h to obtain a suspension, dry the suspension for 12 h, and then vacuum dry for 12 h to obtain a sample powder;

[0061] S5: The sample powder in S2 is pressed into a sheet-like sample by a die press at 20 MPa;

[0062] S6: The sample in S3 is placed in a tubular furnace under an argon atmosphere for carbonization. The carbonization conditions are: keeping the temperature at 400°C for 1 hour, then raising the temperature to 1300°C and carbonizing for 2 hours.

[0063] Comparative Example 2

[0064] The preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 2 is roughly the same as that of Example 1. The difference between the preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 2 and Example 1 is that the carbonization conditions of Comparative Example 2 are: keeping warm at 450°C for 1h, and then carbonizing at 1300°C for 2h.

[0065] Comparative Example 3

[0066] The preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 3 comprises the following steps:

[0067] S1: Grind the bituminous coal in a ball mill for 10 h to obtain coal powder, 10 g of the coal powder was passed through a 200 mesh sieve, and then placed in a vacuum drying oven at 120 °C for 12 h;

[0068] S2: Add the dried coal powder into a flask containing 200 mL of 5M hydrochloric acid solution, place the flask in an oil bath, set the temperature to 80°C and use mechanical stirring. A condenser tube needs to be installed on the flask to remove inorganic impurities. After reacting for 12 hours, filter and wash with deionized water until neutral to obtain solid particles;

[0069] S3: Add the solid particles into a beaker containing 200 mL of 5M HF solution, place the beaker in an oil bath and heat to 80°C, seal the beaker with plastic wrap, stir magnetically for 12 hours, filter, wash with deionized water until neutral, and vacuum dry at 120°C to obtain the impurity-free coal powder;

[0070] S4: Add 5 g of the impurity-removed coal powder and 5 g of sodium gluconate into a beaker containing 200 mL of deionized water, react in an oil bath at 100°C for 2 h to obtain a suspension, dry the suspension for 12 h, and then vacuum dry it for 12 h to obtain a sample powder;

[0071] S5: The sample powder in S4 is pressed into a sheet-like sample by a die press at 20 MPa;

[0072] S6: The sample in S5 is placed in a tubular furnace under an argon atmosphere for carbonization. The carbonization conditions are: keeping the temperature at 500°C for 1 hour, then raising the temperature to 1300°C and carbonizing for 2 hours.

[0073] Comparative Example 4

[0074] The preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 4 is substantially the same as that of Example 1. The difference between the preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 4 and Example 1 is that in Comparative Example 4, sodium gluconate is replaced by sodium alginate.

[0075] Comparative Example 5

[0076] The preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 5 is roughly the same as that of Example 1. The difference between the preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 4 and Example 1 is that the carbonization conditions of Comparative Example 5 are: keeping warm at 350°C for 1h, and then carbonizing at 1100°C for 2h.

[0077] Comparative Example 6

[0078] The preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 6 is roughly the same as that of Example 1. The difference between the preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 6 and Example 1 is that in Comparative Example 6, sodium gluconate is replaced by calcium gluconate.

[0079] Comparative Example 7

[0080] The preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 7 is roughly the same as that of Example 1. The difference between the preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 7 and Example 1 is that S4 of Comparative Example 7 is prepared by adding 5 g of impurity-removed coal powder and 5 g of sodium gluconate into a ball mill, and then ball milling at 400 rpm for 6 hours to obtain a sample powder.

[0081] Comparative Example 8

[0082] The preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 8 is roughly the same as that of Example 1. The difference between the preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 8 and Example 1 is that in Comparative Example 8, sodium gluconate is replaced by carboxymethyl cellulose.

[0083] Comparative Example 9

[0084] The preparation method of the high-capacity carbon-coated coal-based hard carbon material of Comparative Example 9 comprises the following steps:

[0085] S1: Grind the bituminous coal in a ball mill for 10 h to obtain coal powder, 10 g of the coal powder was passed through a 200 mesh sieve, and then placed in a vacuum drying oven at 120 °C for 12 h;

[0086] S2: Add the dried coal powder into a flask containing 200 mL of 5M hydrochloric acid solution, place the flask in an oil bath, set the temperature to 80°C and use mechanical stirring. A condenser tube needs to be installed on the flask to remove inorganic impurities. After reacting for 12 hours, filter and wash with deionized water until neutral to obtain solid particles;

[0087] S3: Add the solid particles into a beaker containing 200 mL of 5M NaOH solution, place the beaker in an oil bath and heat to 80°C, seal the beaker with plastic wrap, stir the mixture under magnetic stirring for 12 hours, filter and wash with deionized water until acidic, and dry under vacuum at 120°C to obtain the impurity-free coal powder;

[0088] S4: The impurity-removed pulverized coal is placed in a tubular furnace under an argon atmosphere for carbonization. The carbonization conditions are: keeping at 350°C for 1 hour, and then carbonizing at 1300°C for 2 hours.

[0089] from Figure 2 It can be seen that the first coulombic efficiency of Example 1 is increased to 58.8%, while the first coulombic efficiency of Comparative Example 9 is only 38%, indicating that the modified coal powder can improve the first coulombic efficiency of the battery. Figure 3 and Figure 4 It can be seen that the diameter of the coal-based hard carbon material particles in Example 1 is relatively uniform, at about 2 μm, while the diameter of the coal-based hard carbon material particles in Comparative Example 9 is about 10 μm. The larger particles of the coal-based hard carbon material are not conducive to the dispersion of the negative electrode slurry when preparing the negative electrode sheet.

[0090] from Figure 5 It can be seen that different platform capacities appear in Comparative Examples 1-3 due to different insulation temperatures, which is because different insulation temperatures have a greater impact on the cross-linking reaction. Figure 6It can be seen that after the carbonization temperature is lowered in Comparative Example 5, it is not conducive to the platform capacity of the coal-based hard carbon material. After replacing sodium gluconate with sodium alginate in Comparative Example 6, the capacity is improved, but the 0.1-1V capacity is still low. After the ball milling is changed to Comparative Example 7, the sodium gluconate and coal powder are not evenly dispersed, resulting in a low capacity of the coal-based hard carbon material.

Claims

1. A method for preparing a high-capacity carbon-coated coal-based hard carbon material, characterized in that: The following steps are involved: The coal-based material is ground to obtain coal powder, the coal powder is subjected to acid-base purification and drying treatment to obtain impurity-removed coal powder, the impurity-removed coal powder and sodium gluconate are added to a solvent and reacted under heating conditions to obtain a suspension, and the suspension is dried and carbonized to obtain the product.

2. The method for preparing a high-capacity carbon-coated coal-based hard carbon material according to claim 1, characterized in that: The mass ratio of the coal powder after impurities removal to the sodium gluconate is 1:0.8 to 1:1; the solvent is water, and 30 to 60 mL of the solvent is added for every gram of the coal powder after impurities removal.

3. The method for preparing a high-capacity carbon-coated coal-based hard carbon material according to claim 1, characterized in that: The reaction temperature of the impurity-removed coal powder and the sodium gluconate is 50-150° C., and the reaction time is 1-4 hours.

4. The method for preparing a high-capacity carbon-coated coal-based hard carbon material according to claim 1, characterized in that: The carbonization is carried out under an inert gas, and the steps of the carbonization are: keeping warm at 200-350° C. for 1-4 hours, and then carbonizing at 1200-1500° C. for 1-3 hours.

5. The method for preparing a high-capacity carbon-coated coal-based hard carbon material according to claim 4, characterized in that: The inert gas is argon.

6. The method for preparing a high-capacity carbon-coated coal-based hard carbon material according to claim 1, characterized in that: The steps of acid-base purification and drying are: washing the coal powder with an acid solution and then washing it with water until it is neutral, washing it with an alkali solution and then washing it with water until it is neutral, and then drying it.

7. The method for preparing a high-capacity carbon-coated coal-based hard carbon material according to claim 1, characterized in that: The coal-based material is bituminous coal; the coal-based material is ball-milled to obtain coal powder, and the coal powder is sieved through a 100-400 mesh sieve, dried, and then subjected to acid-base purification and drying treatment.

8. A high-capacity carbon-coated coal-based hard carbon material, characterized in that: The high-capacity carbon-coated coal-based hard carbon material is prepared by the preparation method of any one of claims 1 to 7.

9. A negative electrode plate, characterized in that: Contains the high-capacity carbon-coated coal-based hard carbon material as described in claim 8.

10. A sodium ion battery, characterized in that: Contains the negative electrode sheet as described in claim 9.

Citation Information

Cited By

  • Preparation method and application of high-rate hard carbon material

    CN121202106A